RESULTS OF DIAGNOSTICS AND TREATMENT OF ADRENOCORTICAL CANCER - P. N. Romashchenko; N. A. Maistrenko; R. V. Orlova; A. I. Babich (Вестник хирургии имени И.И. Грекова)
The results of examination and treatment of 96 patients with adrenocortical cancer (ACC) were analyzed. Local forms of ACC (I and II stages (T1-2N0M0) were found in 19 patients, locally advanced forms (III stage (T1-4N1M0; T3-4N0M0) - in 62 cases and metastatic forms of ACC (IV stage (TxNxM1) - in 15 patients. The diagnostic approach to ACC was optimized. It allowed identifying ACC on early stages of oncological process and staging of oncological process preoperatively in order to justify a rational treatment option. Surgical interventions were performed on 85 patients. The authors used an open access in 75 patients and endovideosurgical - in 10. The most common way of surgery was to remove an affected adrenal gland with fat of upper paranephrium and regional for adrenal lymph nodes (n=56). The adrenalectomy and nephrectomy were fulfilled on 23 patients. A removal of the right adrenal with tumor and thrombus of the interior vena cava was carried out in 2 patients. Some patients (n=4) underwent the explorative interventions. Combined treatment was applied in 28 patients with ACC of III stage. This gave a possibility to increase their life-span from 17,5±8,4 to 36,3±6 months. The overall 3-year survival rate for patients with ACC was 41,2% and 5-year survival observed in 18,7%. An application of modified treatment-and-diagnostics algorithm allowed increasing detection of patients with local and locally advanced forms of ACC in 2,5 times. Therefore, the application of rational treatment options have reduced the number of intraoperative complications from 38,8% to 10,2% and postoperative complication rates- from 61,1% to 20,4%, the lethality rate - from 7,1% to 0% in early postoperative period. These measures have increased the life-span and life quality in 2 times.